Negativa de inscripción de derechos y acciones de predios rurales en Santo Domingo - Carrión Ortíz, Edgar Patricio (2025)
This research focuses on the issue of the inability to register rights and actions over rural land parcels smaller than one hectare in the Property Registry of Santo Domingo. This restriction arises from the prohibition established in Article 269 of the Ordinance on the Development and Land Use Plan of the Canton, which prevents the registration of public deeds for the sale of rural land with an area smaller than this limit. The objective of this study is to examine the legal effects of this refusal to register. To that end, a qualitative methodology with a descriptive approach has been chosen, involving a detailed examination of relevant documentation. Addressing the issue related to the registration process of rights and shares over rural properties under one hectare is crucial and should be undertaken from the perspective of experts in registry matters. This will help to highlight the lack of adequate legal regulations governing the partition or subdivision of rural land. In conclusion, it is important to note that the refusals to register are based on the provisions of the Civil Code. Therefore, the authorities responsible for issuing decisions in such matters are civil judges, who must act through procedures that should be provided for in the Registry Law. However, the current legal framework lacks such a legal mechanism, which undermines the principles of legal certainty, promptness, and procedural economy for users of the registration service.